Entre o planejado e o verossímil: redes sociais como possibilidade para o ensino de língua portuguesa - Furtado, Érika Almeida (2019)
This paper aims to investigate how working with discursive genres that circulate in social networks can enable didactic-methodological strategies for teaching Portuguese language in the classroom, meeting a discursive and dialogical approach. In the focus given to discursive genres, these were treated as different forms of expression defined by socio-communicative properties that arise in a given context, meeting the needs of individuals. This is a qualitative research, with the realization a case study were carried out, we counted on the participation of two distinct subjects: students from a 1st / 2nd grade High School class and Portuguese Language teachers from this same school class. We highlight as theoretical reference the studies of Mikhail Bakhtin (2003; 2017), regarding a dialogic-discursive perspective of language; Geraldi (1997; 2006) and Marcuschi (2005, 2008), considering the issues that permeate teaching from a discursive perspective; Alarcão (2001) regarding the constitution of the reflective teacher; Levy (1993, 1999) and Rojo (2006, 2007) considering the aspects related to the use as a didactic-pedagogical resource of new technologies and digital literacy. To the search, questionnaires and a semi-structured interview were applied, as well as participation the development of a pedagogical practice in the classroom. We evidence that students and teachers have knowledge and use digital technologies outside the school context daily, because within this context the use is minimal. We conclude that there is a possibility of social networks working in the classroom as a didactic methodological resource in the teaching of the Portuguese language. However, the use of this support and the technologies that engender it, in itself, does not guarantee the effectiveness of an approach. discursive in language teaching, since the teacher's conception of language and, consequently, his concepts of text and subject, significantly interfere in his pedagogical practice, being able to transform the proposed activities into purely structuralist practices, not differing from exercises. worked in this same perspective, through didactic resources that are already part of the school routine